Fungsi dan Makna Ritus Tae Loas di Kampung Wangkung - Haryanto, Elandus; Kaler, I Ketut; Sama, I Nyoman (Sunari Penjor : Journal of Anthropology; Vol 4 No 1 (2020)DO - 10.24843/SP.2020.v4.i01.p01, 2021)
Rite tae loas is a form of a rite of human life cycle in the community of Wangkung village, East Manggarai Regency, NTT. Local people believe that the rite of tae loas related to the life philosophy of Manggarai community especially Wangkung village, namely lampek lima. Lampek  believed to be the life cycle of Manggarai people since mankind was born into the world until finally died. The research aims to find out: (1) tae loas Rite procession in Wangkung village and (2) the function and meaning of tae loas rite in Wangkung village. Research using qualitative descriptive methods, including data collection with participatory observation, in-depth interviews, library studies and data analysis. The results of the society conducted tae loas Judging from determining the time of ceremony, place of ceremony, the person involved in the ceremony, and the phases of the procedure. Rite Tae Loas carried out the community of Wangkung village has a function and meaning for the life of its people. Tae loas rite function, namely tae loas rites as the inaugural ceremony and the appointment of baby in a rummy, become a member of indigenous peoples, to determine the identity of infants and community solidarity. The meaning of the rite tae loas, namely religious significance, kinship meaning and educational significance.